Diagnosis of latent tuberculosis infection among pediatric household contacts of Iranian tuberculosis cases using tuberculin skin test, IFN- γ release assay and IFN-γ-induced protein-10 - Ghanaie, Roxana Mansour; Karimi, Abdollah; Azimi, Leila; James, Seddon; Nasehi, Mahshid; Mishkar, Abolfazl Panahi; Sheikhi, Mahnaz; Fallah, Fatemeh; Tabatabaei, Sedigheh Rafiei; Hoseini-Alfatemi, Seyedeh Mahsan (BMC pediatrics, 2021)
Background Although the World Health Organization has recommended the diagnosis and prophylactic treatment of latent tuberculous infection (LTBI) in child household contacts of tuberculosis (TB) cases, the national programs in high-burden TB regions rarely implement adequate screening of this high-risk group, mainly because of resource limitations. We aimed to evaluate the prevalence of LTBI among pediatric household contacts of TB cases in two high-burden provinces in Iran. Methods We conducted a cohort study in children who had been in household contact with a TB index. All subjects were assessed for active TB disease. For LTBI diagnosis, tuberculin skin test (TST) and QuantiFERON®-TB Gold Plus (QFT-Plus) were performed at the time of the index TB case diagnosis, as well as, 3, 12, and 18 months, if the first results were negative. In addition, interferon-γ-induced protein-10(IP-10) concentrations were measured for all participants. Results A total of 230 children were enrolled, who had contact with an index TB case. Three contacts were diagnosed with active TB. According to the TST/QFT-Plus results, 104 (45.2%) children were identified with LTBI during our study. Significantly increased IP-10 levels were found in LTBI patients compared to healthy contacts. Accordingly, more than 50% of LTBI contacts and about 10% of healthy contacts were considered as IP-10-positive. Conclusion This study alarmingly illustrates a high prevalence of LTBI among Iranian children exposed to TB cases. We, therefore, emphasize that the children living in close contact with an infectious TB case should be screened effectively and receive prophylactic therapy.